Put the steps in order that are used to solve the following systems of equations by substitution.

{−7x −2y = −13x − 2y = 11

−7(2y+11)−2y=−13

(3,−4)

x−2y=11→ x=2y+11

−16y−77=−13

−14y−77−2y=−13

x=2(−4)+11→ x=3

1 answer

1. Solve one equation for one variable (in this case, solve x=2y+11 from the second equation)
2. Substitute the solved equation into the other equation (in this case, substitute x=2y+11 into the first equation)
3. Solve the resulting equation for the remaining variable (in this case, solve for y)
4. Substitute the solved variable into either of the original equations (in this case, substitute y=-4 into either of the equations)
5. Solve for the remaining variable (in this case, solve for x)
6. Check the solution by plugging in the values for x and y into both original equations to ensure they are true.